###### Advertisements

###### Advertisements

Solve for x : `tan^-1 ((2-"x")/(2+"x")) = (1)/(2)tan^-1 ("x")/(2), "x">0.`

###### Advertisements

#### Solution

Given that

⇒ `tan^-1 ((2-"x")/(2+"x")) = (1)/(2) tan^-1 ("x")/(2)`

⇒ `2tan^-1 ((2-"x")/(2+"x")) = tan^-1 ("x")/(2)`

⇒ `tan^-1 (2((2-"x")/(2+"x")))/(1 - ((2-"x")/(2+"x"))^2) = tan^-1 ("x")/(2)`

⇒ `tan^-1 (4 - x^2)/(4x) = tan^-1 ("x")/(2)`

⇒ `(4 -"x"^2)/(4"x") = ("x")/(2)`

**∴** `"x" = 2/sqrt3 ...[∵ "x" >0]`.

#### APPEARS IN

#### RELATED QUESTIONS

If `sin (sin^(−1)(1/5)+cos^(−1) x)=1`, then find the value of *x*.

Solve for x : tan^{-1} (x - 1) + tan^{-1}x + tan^{-1} (x + 1) = tan^{-1} 3x

If a line makes angles 90°, 60° and θ with *x*, *y* and z-axis respectively, where θ is acute, then find θ.

If `tan^-1(2x)+tan^-1(3x)=pi/4`, then find the value of ‘x’.

Prove `tan^(-1) 2/11 + tan^(-1) 7/24 = tan^(-1) 1/2`

Prove `2 tan^(-1) 1/2 + tan^(-1) 1/7 = tan^(-1) 31/17`

**Write the following function in the simplest form:**

`tan^(-1) (sqrt((1-cos x)/(1 + cos x))), x < pi`

**Write the following function in the simplest form:**

`tan^(-1) x/(sqrt(a^2 - x^2))`, |x| < a

**Find the value of following:**

`tan 1/2 [sin^(-1) (2x)/(1+ x^2) + cos^(-1) (1-y^2)/(1+y^2)], |x| < 1, y> 0 and xy < 1`

**Find the value of the given expression.**

`sin^(-1) (sin (2pi)/3)`

`sin[pi/3 - sin^(-1) (-1/2)]` is equal to ______.

**Prove that:**

`sin^(-1) 8/17 + sin^(-1) 3/5 = tan^(-1) 77/36`

**Prove that:**

`cos^(-1) 12/13 + sin^(-1) 3/5 = sin^(-1) 56/65`

sin (tan^{–1} x), | x| < 1 is equal to ______.

sin^{–1} (1 – x) – 2 sin^{–1} x = `pi/2` **, **then x is equal to ______.

If cos^{-1} x + cos ^{-1 }y + cos^{ -1} z = π , prove that x^{2} + y^{2} + z^{2} + 2xyz = 1.

If y = `(x sin^-1 x)/sqrt(1 -x^2)`, prove that: `(1 - x^2)dy/dx = x + y/x`

Find the value, if it exists. If not, give the reason for non-existence

`sin^-1 (cos pi)`

Find the value, if it exists. If not, give the reason for non-existence

`tan^-1(sin(- (5pi)/2))`

Find the value, if it exists. If not, give the reason for non-existence

`sin^-1 [sin 5]`

Find the value of the expression in terms of x, with the help of a reference triangle

sin (cos^{–1}(1 – x))

Find the value of the expression in terms of x, with the help of a reference triangle

cos (tan^{–1} (3x – 1))

Find the value of `sin^-1[cos(sin^-1 (sqrt(3)/2))]`

Find the value of `cot[sin^-1 3/5 + sin^-1 4/5]`

Prove that `tan^-1 2/11 + tan^-1 7/24 = tan^-1 1/2`

Prove that `sin^-1 3/5 - cos^-1 12/13 = sin^-1 16/65`

Prove that `tan^-1x + tan^-1y + tan^-1z = tan^-1[(x + y + z - xyz)/(1 - xy - yz - zx)]`

If tan^{–1}x + tan^{–}^{1}y + tan^{–}^{1}z = π, show that x + y + z = xyz

Prove that `tan^-1x + tan^-1 (2x)/(1 - x^2) = tan^-1 (3x - x^3)/(1 - 3x^2), |x| < 1/sqrt(3)`

Solve: `sin^-1 5/x + sin^-1 12/x = pi/2`

Solve: `tan^-1x = cos^-1 (1 - "a"^2)/(1 + "a"^2) - cos^-1 (1 - "b"^2)/(1 + "b"^2), "a" > 0, "b" > 0`

Solve: `2tan^-1 (cos x) = tan^-1 (2"cosec" x)`

Choose the correct alternative:

If `sin^-1x + sin^-1y = (2pi)/3` ; then `cos^-1x + cos^-1y` is equal to

Choose the correct alternative:

`sin^-1 3/5 - cos^-1 13/13 + sec^-1 5/3 - "cosec"^-1 13/12` is equal to

Choose the correct alternative:

`sin^-1 (tan pi/4) - sin^-1 (sqrt(3/x)) = pi/6`. Then x is a root of the equation

Choose the correct alternative:

sin^{–1}(2 cos^{2}x – 1) + cos^{–}^{1}(1 – 2 sin^{2}x) =

Choose the correct alternative:

If |x| ≤ 1, then `2tan^-1x - sin^-1 (2x)/(1 + x^2)` is equal to

Choose the correct alternative:

If `sin^-1x + cot^-1 (1/2) = pi/2`, then x is equal to

Evaluate `cos[sin^-1 1/4 + sec^-1 4/3]`

Prove that cot^{–1}7 + cot^{–1}8 + cot^{–1}18 = cot^{–1}3

Solve the equation `sin^-1 6x + sin^-1 6sqrt(3)x = - pi/2`

Prove that `sin^-1 8/17 + sin^-1 3/5 = sin^-1 7/85`

If cos^{–1}α + cos^{–1}β + cos^{–1}γ = 3π, then α(β + γ) + β(γ + α) + γ(α + β) equals ______.

The number of real solutions of the equation `sqrt(1 + cos 2x) = sqrt(2) cos^-1 (cos x)` in `[pi/2, pi]` is ______.

If y = `2 tan^-1x + sin^-1 ((2x)/(1 + x^2))` for all x, then ______ < y < ______.

The value of cot `("cosec"^-1 5/3 + "tan"^-1 2/3)` is ____________.

If x = a sec θ, y = b tan θ, then `("d"^2"y")/("dx"^2)` at θ = `π/6` is:

Simplest form of `tan^-1 ((sqrt(1 + cos "x") + sqrt(1 - cos "x"))/(sqrt(1 + cos "x") - sqrt(1 - cos "x")))`, `π < "x" < (3π)/2` is:

The value of `"tan"^-1 (1/2) + "tan"^-1(1/3) + "tan"^-1(7/8)` is ____________.

`"tan" (pi/4 + 1/2 "cos"^-1 "x") + "tan" (pi/4 - 1/2 "cos"^-1 "x") =` ____________.

`"cos"^-1["cos"(2"cot"^-1(sqrt2 - 1))]` = ____________.

Solve for x : `{"x cos" ("cot"^-1 "x") + "sin" ("cot"^-1 "x")}^2` = `51/50

The Government of India is planning to fix a hoarding board at the face of a building on the road of a busy market for awareness on COVID-19 protocol. Ram, Robert and Rahim are the three engineers who are working on this project. “A” is considered to be a person viewing the hoarding board 20 metres away from the building, standing at the edge of a pathway nearby. Ram, Robert and Rahim suggested to the firm to place the hoarding board at three different locations namely C, D and E. “C” is at the height of 10 metres from the ground level. For viewer A, the angle of elevation of “D” is double the angle of elevation of “C” The angle of elevation of “E” is triple the angle of elevation of “C” for the same viewer. Look at the figure given and based on the above information answer the following:

Measure of ∠DAB = ________.

The Government of India is planning to fix a hoarding board at the face of a building on the road of a busy market for awareness on COVID-19 protocol. Ram, Robert and Rahim are the three engineers who are working on this project. “A” is considered to be a person viewing the hoarding board 20 metres away from the building, standing at the edge of a pathway nearby. Ram, Robert and Rahim suggested to the firm to place the hoarding board at three different locations namely C, D and E. “C” is at the height of 10 metres from the ground level. For viewer A, the angle of elevation of “D” is double the angle of elevation of “C” The angle of elevation of “E” is triple the angle of elevation of “C” for the same viewer. Look at the figure given and based on the above information answer the following:

Measure of ∠EAB = ________.

The Government of India is planning to fix a hoarding board at the face of a building on the road of a busy market for awareness on COVID-19 protocol. Ram, Robert and Rahim are the three engineers who are working on this project. “A” is considered to be a person viewing the hoarding board 20 metres away from the building, standing at the edge of a pathway nearby. Ram, Robert and Rahim suggested to the firm to place the hoarding board at three different locations namely C, D and E. “C” is at the height of 10 metres from the ground level. For viewer A, the angle of elevation of “D” is double the angle of elevation of “C” The angle of elevation of “E” is triple the angle of elevation of “C” for the same viewer. Look at the figure given and based on the above information answer the following:

𝐴' Is another viewer standing on the same line of observation across the road. If the width of the road is 5 meters, then the difference between ∠CAB and ∠CA'B is ______.

`tan^-1 1/2 + tan^-1 2/11` is equal to

The Simplest form of `cot^-1 (1/sqrt(x^2 - 1))`, |x| > 1 is

What is the value of cos (sec^{–1}x + cosec^{–1}x), |x| ≥ 1

Find the value of `cos^-1 (1/2) + 2sin^-1 (1/2) ->`:-

What is the simplest form of `tan^-1 sqrt(1 - x^2 - 1)/x, x ≠ 0`

The value of `tan^-1 (x/y) - tan^-1 (x - y)/(x + y)` is equal to

`sin^-1(1 - x) - 2sin^-1 x = pi/2`, tan 'x' is equal to

Find the value of `sin^-1 [sin((13π)/7)]`

`50tan(3tan^-1(1/2) + 2cos^-1(1/sqrt(5))) + 4sqrt(2) tan(1/2tan^-1(2sqrt(2)))` is equal to ______.

`tan(2tan^-1 1/5 + sec^-1 sqrt(5)/2 + 2tan^-1 1/8)` is equal to ______.

The set of all values of k for which (tan^{–1} x)^{3} + (cot^{–1} x)^{3} = kπ^{3}, x ∈ R, is the internal ______.

If `cos^-1(2/(3x)) + cos^-1(3/(4x)) = π/2(x > 3/4)`, then x is equal to ______.

If `tan^-1 ((x - 1)/(x + 1)) + tan^-1 ((2x - 1)/(2x + 1)) = tan^-1 (23/36)` = then prove that 24x^{2} – 23x – 12 = 0